Modelo Elétrico Alternativo e Circuito de Condicionamento com Compensação do efeito da Temperatura para Sensores ISFET sensíveis a pH - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
In recent decades, special attention has been paid to the study of silicon-based biosensors in the field of bioanalytical applications, due to their favorable operating characteristics, which include: good sensitivity, processing speed, miniaturization and low cost. Among these, the Ion Sensing Field Effect Transistor (ISFET) is one of the most popular biosensors and is regarded as the first miniaturized silicon-based chemical sensor. The ISFET conventionally used as a pH sensor has been widely used to measure the concentration of hydrogen ions of a substance (H + or OH-) [1] [2]. This work presents an alternative model for ISFET sensors based on the simulation limitations of the classic model presented by Martinoia [3] [4]. The alternative model can be used in both permanent and transient regime simulations, including also the effect of temperature, where it is desired to investigate the electrical signal resulting from a reading circuit used for the initial treatment of the signal transduced by a pH sensitive ISFET sensor. The electrochemical stage of an ISFET is responsible for emulating the device's ion sensitivity. The alternative model is able to represent this stage through a simpler circuit topology than those found in the literature, without loss of generality. The simulation results using the proposed ISFET model are compatible with those presented in the literature, thus affirming its effectiveness. This work also presents a signal conditioning circuit for ISFET sensors sensitive to pH with temperature compensation. As compared to the conventional circuit topologies found in the literature, besides the temperature effect compensation, the proposed analog interface has at least two advantages. The first is related to simplicity and, consequently, to the reduced size of the circuit; the second is the additional gain conferred to the sensor output signal. Its performance was investigated through simulations performed in SPICE (Simulation Program with Integrated Circuit Emphasys) simulator using the BSIM3v3 models. The BSIM3 (Berkeley Short Channel Insulated field effect transistor Model) models are public models developed at the University of Berkeley, California; such models are widely used in simulations of analog and digital circuits that use MOS devices of submicron dimensions. The conventional reading circuit topologies for ISFET sensors do not confer sensitivity gain and have their output limited to the sensitivity of the transducer element, as predicted by the Nernst model [2] and observed by Martinoia [3] [4]. The simulation results show that in its basic design, the circuit topology proposed in this work grants additional gains to the sensor output signal, increasing its sensitivity up to forty times the theoretical limit of Nernst; in an alternative design the gain granted reaches up to ten times the sensor limit, but with the compensation of the effect of the temperature.
Alternative Electrical Model and Temperature Efificient Conditioning Circuit pH Sensitive ISFET Sensors
Keywords: ISFET; Sensor de pH; Limite de Nernst; Compensação de Temperatura; ENGENHARIAS: ENGENHARIA ELÉTRICA